The cumulative effect of the combined action of miR-101 and curcumin in a liposome on a model of Alzheimer’s disease in mononuclear cells - Sokolik, Victoria Vasilevna; Berchenko, Olga Grigorievna (Frontiers in Cellular Neuroscience, 2023)
The leading pathological mechanisms of Alzheimer's disease (AD) are amyloidosis and chronic inflammation. The study of new therapeutic drugs of the corresponding action, in particular miRNAs and curcominoids, as well as methods for their packaging, is topical. The aim of the work was to study the effect of miR-101+curcumin in a single liposome in a cellular AD model. A model of Alzheimer's disease was made by incubating a suspension of mononuclear cells with aggregates of beta-amyloid peptide 1-40 (Aβ40) for 1 h. The effect of the subsequent application of liposomal (L) preparations miR-101, curcumin (CUR) and miR-101+ CUR was analyzed over time of 1 h, 3 h, 6 h and 12 h. A decrease in the level of endogenous Aβ42 under the influence of L(miR-101+ CUR) was revealed during the entire incubation period (1-12 h), the first part of which was overlapped due to inhibition of mRNAAβPP translation by miR -101 (1-3 h), and the second – by inhibition of mRNAAβPP transcription by curcumin (3-12 h), the minimum concentration of Aβ42 was recorded at 6 h. The cumulative effect of the combination drug L(miR-101+ CUR) was manifested in the suppression of the increase in the concentration of TNFα and IL-10 and a decrease in the concentration of IL-6 during the entire incubation period (1–12 h). Thus, miR-101+CUR in one liposome enhanced each other's antiamyloidogenic and anti-inflammatory effects in a cell model of Alzheimer's disease.